Level of knowledge and attitude of primary care physicians in Eastern Anatolian cities in relation to child abuse and neglect - Açik, Y; Deveci, SE; Oral, R (Academic Press Inc Elsevier Science, 2004)
Background. Child abuse and neglect is not a new phenomenon. It has always existed in every nation and culture in one form or another. The aim of this study was to determine the level of knowledge and attitude toward child abuse and neglect of primary care physicians serving in eastern Turkish cities. Methods. The study was done in four Eastern Turkish cities involving Elazig, Tunceli, Malatya, and Bingol. All the primary care physicians serving in these cities were contacted. Of 266 primary care physicians, 175 replied (65.8% reply rate) and participated in the study. Results. Most of the participated primary care physicians did not have adequate knowledge about physical assessment of suspected child abuse and neglect. Those physicians serving in primary care centers had better knowledge than those serving in Mother-Child Health and Family Planning Centers. Conclusions. Results from this study indicate that primary care physicians working in the eastern cities of Turkey do not have adequate knowledge and proper attitudes toward the identification and reporting of suspected child abuse. There is a need for educational programs to primary care physicians and other health personals working with child abuse and neglect to increase their knowledge and skills in detection, assessment, reporting, treatment, and prevention of child abuse and neglect. (C) 2004 The Institute For Cancer Prevention and Elsevier Inc. All rights reserved.
Keywords: primary care physician; child abuse and neglect; knowledge; attitude